Impact of Rapid Vaccination on Sars-Cov-2 Genomic Diversity: An Intervention to Minimise the Public Burden of the Pandemic - Amirah Azzeri; Shuhaila Mat-Sharani; Danish A/L Kumareahsan; Ismatul Nurul Asyikin Ismail; Muhamad Arif Mohamad Jamali; Liyana Azmi (Malaysian Journal of Public Health Medicine, 2024)
Indexed by Scopus/MyCite